Buzz at workplaces in knowledge-intensive service production: Spatial settings of temporary spatial proximity. (October 2019) - Growe, Anna
The objective of this paper is to understand temporary spatial proximity beyond temporary clusters, and to analyse rationales for the use of various spatial settings for temporary spatial proximity in the work processes of knowledge-intensive services. To contrast different types of temporary spatial proximity two basic types, 'Meet and Mingle' and 'Move and Manage', are identified. On the basis of qualitative interviews in knowledge-intensive sectors in six German cities, the distinct use of three types of spatial settings (workplaces, transit places and retreat places) to create the targeted temporary spatial proximity type of 'Move and Manage' is analysed. The paper discusses how such settings contribute to creating a specific atmosphere to support the work processes of knowledge-intensive services.